Contacting out-of-hours primary care or emergency medical services for time-critical conditions - impact on patient outcomes - Morten Breinholt Søvsø; Morten Bondo Christensen; Bodil Hammer Bech; Helle Collatz Christensen; Erika Frischknecht Christensen; Linda Huibers (BMC, 2019)
Abstract Background Out-of-hours (OOH) healthcare services in Western countries are often differentiated into out-of-hours primary healthcare services (OOH-PC) and emergency medical services (EMS). Call waiting time, triage model and intended aims differ between these services. Consequently, the care pathway and outcome could vary based on the choice of entrance to the healthcare system. We aimed to investigate patient pathways and 1- and 1-30-day mortality, intensive care unit (ICU) stay and length of hospital stay for patients with acute myocardial infarction (AMI), stroke and sepsis in relation to the OOH service that was contacted prior to the hospital contact. Methods Population-based observational cohort study during 2016 including adult patients from two Danish regions with an OOH service contact on the date of hospital contact. Patients <18 years were excluded. Data was retrieved from OOH service databases and national registries, linked by a unique personal identification number. Crude and adjusted logistic regression analyses were performed to assess mortality in relation to contacted OOH service with OOH-PC as the reference and cox regression analysis to assess risk of ICU stay. Results We included 6826 patients. AMI and stroke patients more often contacted EMS (52.1 and 54.1%), whereas sepsis patients predominately called OOH-PC (66.9%). Less than 10% (all diagnoses) of patients contacted both OOH-PC & EMS. Stroke patients with EMS or OOH-PC & EMS contacts had higher likelihood of 1- and 1-30-day mortality, in particular 1-day (EMS: OR = 5.33, 95% CI: 2.82-10.08; OOH-PC & EMS: OR = 3.09, 95% CI: 1.06-9.01). Sepsis patients with EMS or OOH-PC & EMS contacts also had higher likelihood of 1-day mortality (EMS: OR = 2.22, 95% CI: 1.40-3.51; OOH-PC & EMS: OR = 2.86, 95% CI: 1.56-5.23) and 1-30-day mortality. Risk of ICU stay was only significantly higher for stroke patients contacting EMS (EMS: HR = 2.38, 95% CI: 1.51-3.75). Stroke and sepsis patients with EMS contact had longer hospital stays. Conclusions More patients contacted OOH-PC than EMS. Sepsis and stroke patients contacting EMS solely or OOH-PC & EMS had higher likelihood of 1- and 1-30-day mortality during the subsequent hospital contact. Our results suggest that patients contacting EMS are more severely ill, however OOH-PC is still often used for time-critical conditions.